New Endothelial Mechanisms in Glomerular (Patho)biology and Proteinuria Development Captured by Intravital Multiphoton Imaging - Gyarmati, Georgina; Jacob, Chaim O.; Peti-Peterdi, János (Frontiers in Medicine, 2021)
In the past two decades, intravital imaging using multiphoton microscopy has provided numerous new visual and mechanistic insights into glomerular biology and disease processes including the function of glomerular endothelial cells (GEnC), podocytes, and the development of proteinuria. Although glomerular endothelial injury is known to precede podocyte damage in several renal diseases, the primary role of GEnCs in proteinuria development received much less attention compared to the vast field of podocyte pathobiology. Consequently, our knowledge of GEnC mechanisms in glomerular diseases is still emerging. This review highlights new visual clues on molecular and cellular mechanisms of GEnCs and their crosstalk with podocytes and immune cells that were acquired recently by the application of multiphoton imaging of the intact glomerular microenvironment in various proteinuric disease models. New mechanisms of glomerular tissue remodeling and regeneration are discussed based on results of tracking the fate and function of individual GEnCs using serial intravital multiphoton imaging over several days and weeks. The three main topics of this review include (i) the role of endothelial injury and microthrombi in podocyte detachment and albumin leakage via hemodynamic and mechanical forces, (ii) the alterations of the endothelial surface layer (glycocalyx) and its interactions with circulating immune cells in lupus nephritis, and (iii) the structural and functional remodeling and regeneration of GEnCs in hypertension, diabetes and other experimental injury conditions. By the comprehensive visual portrayal of GEnCs and the many other contributing glomerular cell types, this review emphasizes the complexity of pathogenic mechanisms that result in proteinuria development.